Glomerular deposition of properdin in acute and chronic glomerulonephritis with hypocomplementemia - Westberg, N. Gunnar (1971)
Kidney tissue from 97 patients was studied by immunofluorescent techniques using antiserum to purified properdin. All patients with acute poststreptococcal glomerulonephritis showed deposition of properdin and the third component of complement (C3), either as “humps” on the basement membrane, or in the mesangium. In all cases of chronic membranoproliferative glomerulonephritis, properdin and C3 were localized in the glomeruli, most commonly in a lobular pattern on the basement membrane. Activation of C3 by the properdin system may explain the depressed serum levels of C3 and terminal complement components even though levels of earlier components are normal, and the deposition of C3, often without immunoglobulins, in the kidneys of patients with acute glomerulonephritis or chronic membranoproliferative glomerulonephritis.